Skink stargazing: On the status and taxonomy of the Sphenomorphus stellatus complex (Boulenger, 1900) in Borneo, with the description of a new species (Squamata: Scincidae) - Quah, Evan Seng Huat; L. Lee Grismer (Magnolia Press, 2025)
Sphenomorphus stellatus was once thought to be a wide-ranging species distributed across many parts of Indochina, the Thai-Malay Peninsula and Borneo. However, recent integrative taxonomic studies on the species have revealed its underestimated diversity and new species previously masquerading under this nomen in mainland Southeast Asia. This prompted the re-examination of a specimen identified as S. stellatus from Borneo, and morphological analyses revealed that it is not conspecific with topotypic specimens of the species from Peninsular Malaysia or other congeners of the complex, and is therefore described herein as new. Sphenomorphus striatafaucium sp. nov. can be differentiated from its congeners by a combination of known adult SVL of 57.4 mm; frontal scale undivided; prefrontals in broad contact; four supraoculars; two loreals; eight superciliaries; no enlarged, clear, central window in lower eyelid; seven or eight supralabials; six infralabials; three pairs of chinshields; 24 midbody scale rows; 62 paravertebrals, not wider than other dorsals; 66 ventrals; two enlarged precloacals; 19 subdigital lamellae on fourth toe; and bold and distinct striped pattern on the chin and throat. The discovery of S. striatafaucium sp. nov. increases the number of endemic Sphenomorphus skinks in Borneo to 13 species. The discovery underscores the underestimated diversity of reptile and amphibian species in Borneo, and the need for more concerted efforts to conduct fieldwork and systematic studies to not only improve the understanding of their relationships and ecologies, but also better protect their habitats that are increasingly threatened by anthropogenic pressures. This study also highlights the value of well-curated natural history collections in museums that still harbour new species awaiting discovery.